Variation of leaflet shape from several soybean genotypes and its relation to morphological characters - AYDA KRISNAWATI; M. MUCHLISH ADIE (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Krisnawati A, Adie MM. 2017. The leaflet shape variation from several soybean genotypes in Indonesia. Biodiversitas 18: 359-364. Leaves are part of the plant organs which are of importance to sustain the plant’s life. Generally, each plant has a varied leaflet shape depending on many factors. Soybean, as one of an important source of protein vegetable, has a diverse plant shape among its genotypes. The objective of the research was to evaluate the variation of leaflet shape of 150 soybean (Glycine max L.) genotypes and its relation to another growth and morphological characters. The leaflet shape of 150 soybean genotypes was intensively in Kendalpayak Research Station, Malang (Indonesia) from February to May 2016. This field experiment was conducted in randomized block design with two replicates. The leaf characterization of 150 soybean genotypes using LSI (Leaf Shape Index) method. Analysis of variance of observed soybean genotypes in terms of maturity traits and morphological attributes showed a significantly different among soybean genotypes, except for harvest index (HI) parameter. This indicates that there was variability in morphological characters among of 150 soybean genotypes. The LSI value ranged from 1.40 to 3.05, in average of 2.04. Of all observed soybean genotypes, most of their morphological performance was an intermediate size (110 genotypes), while another 17 genotypes was a broad leaflet, and the rest (23 genotypes) had a narrow leaflet. Genotypes with an intermediate leaflet apparently possessed the different morphological characters of seed in terms of size, weight/plant and yield compared to those leaflet shape of other genotypes. Among the broad leaflet group, accession No. 92 could be prospectively used as a gene donor for improving soybean yield potential in Indonesia due to its high yield production (3.05 t/ha), early maturity, and large seed size. In the group of intermediate leaflet, accession No. 18 could also be used as a potential gene donor showed in its high yield production (3.07 t/ha), early maturity, and large seed size. Meanwhile, the potential gene donor in narrow leaflet group, which could be further used were two genotypes (accession No. 20 and No. 22). Keywords: Glycine max, LSI, morphological characters, gene donor